2023
DOI: 10.1002/biot.202300093
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic hydrogels based on chitosan and carrageenan as promising materials for biological applications

Abstract: In this study, novel crosslinked hydrogels based on chitosan (CS) and carrageenan (CRG) loaded with silver and/or copper nanoparticles (Ag/CuNPs) were prepared through a freeze‐drying (thawing) process to be applied in biological applications comprising wound dressing. These hydrogels showed porous interconnected structures. The influence of the used nanoparticles (NPs) on the antibacterial properties of the CS/CRG hydrogels was explored. Antimicrobial results revealed that both CS/CRG/CuNPs, CS/CRG/AgNPs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Also, bimatellic Ag-Se nanoparticles were synthesized using quercetin and gallic acid, where exhibited outstanding antimicrobial and antitumor activities [ 57 ]. Khalil, Hashem [ 58 ] succeeded in preparing a bimetallic hydrogel based on silver and copper, and results revealed that this hydrogel exhibited promising antibacterial activity toward Escherichia coli , Pseudomonas aeruginosa , Streptococcus mutans , Staphylococcus aureus , Bacillus subtilis , and Candida albicans. Furthermore, Hashem and El-Sayyad [ 59 ] reported that the biosynthesized Ag-ZnO NPs had potential antibacterial activity toward E. coli , P. aeruginosa , B. subtilis , S. aureus , and E. faecalis; also showed antifungal activity against C. albicans , Cryptococcus neoformans , Aspergillus fumigatus , and A. brasiliensis.…”
Section: Resultsmentioning
confidence: 99%
“…Also, bimatellic Ag-Se nanoparticles were synthesized using quercetin and gallic acid, where exhibited outstanding antimicrobial and antitumor activities [ 57 ]. Khalil, Hashem [ 58 ] succeeded in preparing a bimetallic hydrogel based on silver and copper, and results revealed that this hydrogel exhibited promising antibacterial activity toward Escherichia coli , Pseudomonas aeruginosa , Streptococcus mutans , Staphylococcus aureus , Bacillus subtilis , and Candida albicans. Furthermore, Hashem and El-Sayyad [ 59 ] reported that the biosynthesized Ag-ZnO NPs had potential antibacterial activity toward E. coli , P. aeruginosa , B. subtilis , S. aureus , and E. faecalis; also showed antifungal activity against C. albicans , Cryptococcus neoformans , Aspergillus fumigatus , and A. brasiliensis.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan and its derivatives can also form hydrogels, but this requires the creation of a network structure of the molecules of these compounds through physical [44], or chemical cross-linking [45,46]. Hydrogels obtained by preparing blends of chitosan with other polymers seem to be particularly interesting from the point of view of medical applications [47,48] among which the most outstanding are composites formed from positively charged chitosan and negatively charged carrageenan [49][50][51]. The physical hydrogels based on carrageenan/chitosan prepared by electrostatic complexation in aqueous solutions were reported by Papagiannopoulos et al [52].…”
Section: Introductionmentioning
confidence: 99%
“…Obtained polymeric materials were a hemostatic agent and bleeding controller. Khalil et al received carrageenan/chitosan antibacterial hydrogels loaded with silver and/or copper nanoparticles for wound dressing applications [51].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan and its derivatives can also form hydrogels, but this requires the creation of a network structure of the molecules of these compounds through physical [44] or chemical crosslinking [45,46]. Hydrogels obtained by preparing blends of chitosan with other polymers seem to be particularly interesting from the point of view of medical applications [47,48] among which the most outstanding are composites formed from positively charged chitosan and negatively charged carrageenan [49][50][51]. Physical hydrogels based on carrageenan/chitosan prepared by electrostatic complexation in aqueous solutions were reported by Papagiannopoulos et al [52].…”
Section: Introductionmentioning
confidence: 99%
“…Obtained polymeric materials were a hemostatic agent and bleeding controller. Khalil et al pre-pared carrageenan/chitosan antibacterial hydrogels loaded with silver and/or copper nanoparticles for wound dressing applications [51].…”
Section: Introductionmentioning
confidence: 99%